Unraveling the Nanoscale Structure of Organic–Inorganic Hybrid Materials - Jacob Johny; Savarithai Jenani Louis Anandaraj; Carolin Mehrmann; Xin Wei; Ankita Das; Niklas Scheer; Yuke Yang; Walid Hetaba; Petra Ebbinghaus; Ulrich Simon; Rüdiger‐A. Eichel; Florian Hausen; et al. (Advanced Materials Interfaces)
Abstract Metal nanoparticles (NPs) immobilized on molecularly modified supports form versatile hybrid materials, offering extensive combinatorial flexibility and synergistic interactions between the organic and inorganic components, making them ideal for applications such as catalysis, and sensing. In catalysis, e.g., NPs‐ionic liquid combinations are shown to enhance activity, selectivity, and recyclability compared to NPs alone systems, though typically used powder‐based supports often hinder a detailed nanoscale structural analysis for an in‐depth understanding due to undefined surfaces. Here, an approach is developed to transfer such a system onto well‐defined surfaces for extended analysis, demonstrated on a model system composed of an imidazolium/NTf₂ ionic liquid and Ru NPs on Si. A comprehensive characterization suite is applied to probe the material properties at the nano‐ and macroscale including spatial arrangement, molecular orientation, surface homogeneity, hydrophilicity, and work function. The efficacy of the utilized approaches in obtaining a homogeneous ionic liquid monolayer decorated with Ru NPs of controlled distribution is demonstrated. It is identified that the particle deposition disturbs the conformational order of the molecular layer. The presented versatile methodological approach can be broadly expanded to multifunctional hybrid materials composed of metal NPs on molecularly modified supports, unlocking numerous possibilities for knowledge‐driven and rational material design.